2015
DOI: 10.1111/ggi.12557
|View full text |Cite
|
Sign up to set email alerts
|

Early symptoms of Alzheimer's disease in Japan and Taiwan

Abstract: Early symptoms of AD in both countries are different. The frequently reported early symptoms are important for primary physicians and the general population so that they can recognize the disease in the early stage so as to have a better therapeutic outcome. Such efforts would increase the awareness of dementia in the general population. Geriatr Gerontol Int 2016; 16: 797-803.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 27 publications
(40 reference statements)
1
19
2
Order By: Relevance
“…23,24 Furthermore, individuals with AD often offer alternative explanations for such symptoms, which can prevent family members from recognizing the symptoms as characteristic of AD. 23,24 Most families first notice AD progression when the patient shows violently intense behavioral and psychological symptoms of dementia, up to which point the family's lack of concern might have allowed AD to progress. 23,24 The present results might have been influenced by such lack of concern.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23,24 Furthermore, individuals with AD often offer alternative explanations for such symptoms, which can prevent family members from recognizing the symptoms as characteristic of AD. 23,24 Most families first notice AD progression when the patient shows violently intense behavioral and psychological symptoms of dementia, up to which point the family's lack of concern might have allowed AD to progress. 23,24 The present results might have been influenced by such lack of concern.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Most families first notice AD progression when the patient shows violently intense behavioral and psychological symptoms of dementia, up to which point the family's lack of concern might have allowed AD to progress. 23,24 The present results might have been influenced by such lack of concern. In summary, we showed that a greater improvement in scores is associated with lower HDS-R and MMSE scores at the first visit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary symptoms of AD are memory disturbance and disorientation, but people with AD often offer alternative explanations for such symptoms, which can prevent family members from recognising these as symptoms of AD. 8,9 Also, most people with symptoms are averse to taking a cognitive screening test because it can be difficult to accept any resulting diagnosis of cognitive disease. 9 The Hasegawa Dementia Scale-Revised (HDS-R) and Mini-Mental State Examination (MMSE) are commonly used to screen for cognitive disease in Japan.…”
Section: Introductionmentioning
confidence: 99%